Numerical test of finite-size scaling predictions for the droplet condensation-evaporation transition - Nuβbaumer, Andreas; Zierenberg, Johannes; Bittner, Elmar; Janke, Wolfhard (Journal of physics. Conference Series, 2016)
We numerically study the finite-size droplet condensation-evaporation transition in two dimensions. We consider and compare two orthogonal approaches, namely at fixed temperature and at fixed density, making use of parallel multicanonical simulations. The equivalence between Ising model and lattice gas allows us to compare to analytical predictions. We recover the known background density (at fixed temperature) and transition temperature (at fixed density) in the thermodynamic limit and compare our finite-size deviations to the predicted leading-order finite-size corrections.
Gesehen am 13.11.2017